2024
DOI: 10.1101/2024.04.13.589360
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cholinergic interneurons in the nucleus accumbens are a site of cellular convergence for corticotropin release factor and estrogen regulation

Kendra Olson,
Anna E. Ingebretson,
Eleftheria Vogiatzoglou
et al.

Abstract: Cholinergic interneurons (ChIs) act as master regulators of striatal output, finely tuning neurotransmission to control motivated behaviors. ChIs are a cellular target of many peptide and hormonal neuromodulators, including corticotropin releasing factor, opioids, insulin and leptin, which can influence animal behavior by signaling stress, pleasure, pain and nutritional status. However, little is known about how sex hormones via estrogen receptors influence the function of these other neuromodulators. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…We recently demonstrated that loss of Oxtr unmasks sex differences in gene expression in the NAc that are not found in wild-type animals 20 . Thus, the absence of Oxtr signaling during development may also contribute to the differences we observed in patterns of activity in the NAc between male and female Oxtr 1-/- voles 5157 . Alternatively, or in combination, such sex differences in the NAc may arise from Oxtr-regulated inputs to this region that differ between males and females 3,4,5861,6769 .…”
Section: Discussionmentioning
confidence: 96%
“…We recently demonstrated that loss of Oxtr unmasks sex differences in gene expression in the NAc that are not found in wild-type animals 20 . Thus, the absence of Oxtr signaling during development may also contribute to the differences we observed in patterns of activity in the NAc between male and female Oxtr 1-/- voles 5157 . Alternatively, or in combination, such sex differences in the NAc may arise from Oxtr-regulated inputs to this region that differ between males and females 3,4,5861,6769 .…”
Section: Discussionmentioning
confidence: 96%